Important steps towards a big change for lung health: a joint approach by the European Respiratory Society, the European Society of Radiology and their partners to facilitate implementation of the European Union's new recommendations on lung cancer screening - Ward, Brian; Koziar Vašáková, Martina; Robalo Cordeiro, Carlos; Yorgancioğlu, Arzu; Chorostowska-Wynimko, Joanna; Blum, Torsten Gerriet; Kauczor, Hans-Ulrich; Samarzija, Miroslav; Henschke, Claudia; Wheelock, Craig; Grigg, Jonathan; Andersen, Zorana Jovanovic; et al. (ERJ open research, 2023)
Enormous progress has been made on the epic journey towards implementation of lung cancer screening in Europe. A breakthrough for lung health has been achieved with the EU proposal for a Council recommendation on cancer screening. https://bit.ly/3J4O0Jb.